Integrated Cultural-Educational Branding: An Innovative Strategies for Building a Sustainable Image in Islamic Primary School - Sarwo Edy; Syahrul Fauzi; Nenda; Muhammad Zaini El Wahyu (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The emergence of educational institutions shows the concern of society and government. The presence of new educational institutions with their respective advantages and uniqueness will add to the image and characteristics possessed by these educational institutions. In addition, there is very tight competition between educational institutions with each other. Educational institutions should have the right strategy. This study aims to analyze the role of cultural integration in branding strategies specific to Islamic primary education at the Islamic Association of Banjarsari Islamic Community Madrasah, Ciamis and findings that demonstrate how culturally relevant branding has positively impacted stakeholder engagement, student enrollment, and community trust. This study uses a qualitative approach to explorative analysis in natural settings. Data collection techniques by way of observation, interviews, and documentation. Informants included 1 head of Madrasah, 6 educators and educational staff, and 3 guardians of students. Data analysis techniques by means of transcripts, coding, grouping, comparing, and contrasting. Test the validity (verification) of the data is done by using triangulation of sources and techniques. The results of the study show: first, the strategy used to introduce the institution to the public is the existence of attributes on the brand, then the brand provides benefits to all stakeholders, the brand has values, culture, and reflects personality, and the brand gives an impression to service users. Second, the public's attraction to MI PUI Kaum is due to the strength of the brand (brand strength), trying to make the brand the first choice (brand favorability), and creating uniqueness in educational institutions that are not owned by equivalent institutions (brand uniqueness). Third, the implication in efforts to build a brand image at MI PUI Kaum is an increase in the number of students every year, there are contributions to development funds obtained from government agencies, the community, and alumni, increasing public trust in Madrasah Ibtidaiyah Persatuan Umat Islam Kaum Banjarsari.